2017
DOI: 10.1002/2016wr019862
|View full text |Cite
|
Sign up to set email alerts
|

Pore‐scale water dynamics during drying and the impacts of structure and surface wettability

Abstract: Plants and microbes secrete mucilage into soil during dry conditions, which can alter soil structure and increase contact angle. Structured soils exhibit a broad pore size distribution with many small and many large pores, and strong capillary forces in narrow pores can retain moisture in soil aggregates. Meanwhile, contact angle determines the water repellency of soils, which can result in suppressed evaporation rates. Although they are often studied independently, both structure and contact angle influence w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 66 publications
2
23
0
3
Order By: Relevance
“…The plasma treatment is desirable in order for the micromodels to better emulate soil since it results in PDMS having a surface charge similar to quartz sand (Roman and Culbertson, 2006), at least as long as the surface of the PDMS remains covered by water. Observations made by Cruz et al (2017) suggests that the plasma treatment and the emulation of quartz-like surface chemistry are not permanent under unsaturated conditions. In such cases, the macromolecular mobility of the polymer at room temperature allows re-configuration at the surface, and the latter is relatively likely to have properties typical of untreated PDMS.…”
Section: Micromodel Concept and Fabricationmentioning
confidence: 99%
“…The plasma treatment is desirable in order for the micromodels to better emulate soil since it results in PDMS having a surface charge similar to quartz sand (Roman and Culbertson, 2006), at least as long as the surface of the PDMS remains covered by water. Observations made by Cruz et al (2017) suggests that the plasma treatment and the emulation of quartz-like surface chemistry are not permanent under unsaturated conditions. In such cases, the macromolecular mobility of the polymer at room temperature allows re-configuration at the surface, and the latter is relatively likely to have properties typical of untreated PDMS.…”
Section: Micromodel Concept and Fabricationmentioning
confidence: 99%
“…Studies on mixed wettability (i.e., variable contact angle) in soil have shown that surface properties modulate evaporation in soil (Shokri et al, 2008). In prior work, we have shown that pore water is retained longer in micromodels with more hydrophobic surfaces compared with micromodels with identical physical geometries but more hydrophilic surfaces (Cruz et al, 2017).…”
Section: Introductionmentioning
confidence: 72%
“…Key features of the micromodels are (1) the realistic pore scale soil geometry, and (2) precise replication of the geometry from channel to channel and experiment to experiment, and (3) the ease of directly observing the progress of the air-water interface over time. See our prior work (Deng et al, 2015;Cruz et al, 2017;Soufan et al, 2018) for additional details on the creation, validation, and use of the aggregated sandy loam pseudo-2D soil geometry.…”
Section: Soil Micromodel Drying Experimentsmentioning
confidence: 99%
See 2 more Smart Citations